THE MEDIATING ROLE OF GOVERNMENT REGULASTIONS BETWEEN INDIVIDUALS CHARACTERISES, NON-FINANCIAL SERVICES AND ORGANIZATION PERFORMANCE AMONG SMES IN LIBYA - Omer Mohamed Al Zardak; Omar Hamdan Mohammad Alkharabsheh (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
The current study aims to examine the effect of individuals characteristics and non-financial services on the performance of medium-sized and small enterprises (SMEs) in Libya. In addition, this study investigates the mediating role of government regulations that impact the relationship between individuals’ characteristics and non-financial services. A total 392 enterprises participated in this study. Structural equation modelling (SEM) was used in order to examine the causal relationship among the latent variables. The results of the study shows a positive relationship between non-financial services, individuals characteristics, government regulations and SMEs performance. Furthermore, government regulastions had a significant and positive impact on SMEs performance in Libya. On the other hand, the results indecated a insignificant relationship between non-financial services and individuals characteristics influencing SMEs performance. Moreover, the results of the study indicates that government regulations play a mediating role between non-financial services, individuals characterises, and SMEs performance among the employees of SMEs in Libya.